Biochemical, Pathomorphological and Semen Characteristics Analysis in Male Wistar Rats Treated with Withania somnifera Root Extract - Prabu, P.C.; Biravi, K.; Jarisa, S.; Sreepriya, S.; Panchapakesan, S. (Asian Journal of Chemistry, 2014)
Withania somnifera (Ashwagandha) is one of the most popular herbal medicines in the treatment of several diseases. Data on the possible toxic effects of Withania somnifera over male reproductive parameters are not available. In the present study, male Wistar rats were divided into two groups namely, Group I (control administered with distilled water) and Group II (administered orally with Withania somnifera root extract @ 1000 mg/kg body weight for 70 days) of 6 rats each. Blood samples were collected using retro orbital puncture method and various haematological and biochemical parameters were analyzed. No significant changes were found in haematological and biochemical parameters of treated group except for significant decrease in the level of WBC and LYM alone. In the semen characteristics and histopathological analysis, no significant changes were found. The NOEL (No-observed effect level) of Withania somnifera Root extract was concluded as 1000 mg/kg in the male wistar rats.